Congenital Anomalies and their Outcomes in the Neonate Intensive Care Unit in Misurata Center - Assadi, Abdulaleem; Alburki, Salima; Assadi, Moktar; Rajab, Ali; Gadora, Faraj (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objective. Congenital anomalies are a significant cause of infant morbidity and mortality. This study examined the prevalence, types, and associated risk factors of congenital anomalies and their outcomes in infants admitted to the Neonatal Intensive Care Unit (NICU) of Misurata Hospital, Libya, from January to December 2022. Methods. A retrospective review of medical records of infants with congenital anomalies admitted to the NICU of Misurata Hospital from January to December 2022 was conducted. Data on demographics, clinical presentation, maternal factors, and outcomes were collected. Descriptive and statistical analyses were performed. Results. A total of 53 infants with congenital anomalies were included. The mortality rate was 34%. The most prevalent anomalies were congenital heart defects, hypospadias, cleft lip and palate, hydrocephalus, and syndromic baby. Cesarean section, sepsis, maternal age over 35 years, high parity, polyhydramnios, diabetes mellitus, and oligohydramnios were associated with increased risk of mortality or congenital anomalies. Conclusions. Congenital anomalies pose a substantial burden on neonatal health in this setting. Cesarean section, sepsis, and specific maternal factors were identified as risk factors. These findings underscore the importance of tailored care for mothers and infants with congenital anomalies to improve outcomes. الخلفية والهدف. التشوهات الخلقية هي سبب مهم لمرض ووفيات الرضع. فحصت هذه الدراسة انتشار وأنواع وعوامل الخطر المرتبطة بالتشوهات الخلقية ونتائجها لدى الرضع الذين تم إدخالهم إلى وحدة العناية المركزة لحديثي الولادة في مستشفى مصراتة، ليبيا، من يناير إلى ديسمبر 2022. طرق الدراسة. أجريت مراجعة بأثر رجعي للسجلات الطبية للرضع الذين يعانون من تشوهات خلقية تم إدخالهم إلى وحدة العناية المركزة لحديثي الولادة في مستشفى مصراتة من يناير إلى ديسمبر 2022. تم جمع البيانات عن التركيبة السكانية والعرض السريري والعوامل الأمومية والنتائج. تم إجراء التحليلات الوصفية والإحصائية. النتائج. تم تضمين ما مجموعه 53 رضيعًا يعانون من تشوهات خلقية. كان معدل الوفيات 34٪. كانت أكثر التشوهات انتشارًا هي عيوب القلب الخلقية، ونقص تنسج القضيب، والشفة والحنك المشقوقين، واستسقاء الرأس، والطفل المتلازمي. ارتبطت الولادة القيصرية، وتسمم الدم، وعمر الأم فوق 35 عامًا، وارتفاع معدل الولادات، وزيادة السائل الأمنيوسي، ومرض السكري، وقلة السائل الأمنيوسي بزيادة خطر الوفاة أو التشوهات الخلقية. الاستنتاجات. تشكل التشوهات الخلقية عبئًا كبيرًا على صحة الأطفال حديثي الولادة في هذا الوضع. تم تحديد الولادة القيصرية، وتسمم الدم، وعوامل أمومية محددة كعوامل خطر. تؤكد هذه النتائج على أهمية الرعاية المخصصة للأمهات والأطفال الذين يعانون من تشوهات خلقية لتحسين النتائج